Emission benefits in application of alternative fuels on racing car compression ignition engines - Herreros, José M.; Lapuerta, Magín; Lowe, Derek; Njuguna, James A. K. (Cranfield University, 2011)
The depletion of fossil fuels, and the weather-related disasters associated with climate change and greenhouse gas emissions plus the other human health and environmental hazards related to exhaust pollutant emissions demands the use of innovative approaches to reduce fossil fuel consumption. Motorsport industry should become a test-bed, and because of its advertising potential should promote the use of alternative steps to minimize fossil fuel consumption and address associated emission issues. In the short term, some improvements to current powertrain technologies and the use of alternative fuels such as biodiesel or the primary alcohols can reduce fossil fuel dependency and partly decrease their harmful effects. In this study a framework has been developed based on the effect of the different fuel properties to assess their suitability, performance and emission characteristics of different ‘short-term' fuels such as biodiesel and primary alcohols to reduce the use of fossil fuels in motorsport industry. A database is generated to permit the construction and theoretical application of the framework to the specific case of a turbocharged, four-stroke, compression ignition engine with common-rail injection system operating in medium/high temperature engine mode